PENGARUH PAJANAN MERKURI DARI BAHAN MAKANAN TERHADAP KANDUNGAN MERKURI DALAM DARAH IBU MENYUSUI DI DAERAH PERTAMBANGAN EMAS - Asep Iwan Purnawan; Puruhita Niken (Poltekkes Kemenkes Bandung, 2020)
Mercury is commonly used in amalgamation as a gold-binding medium in gold ore processing, which is usually carried out in streams, which produce mercury waste, in the form of metal mercury, organic mercury, and inorganic mercury. The process ofmercurybioaccumulation in the body tissues of animals and plants in a relatively long time, through the food chain from the lowest level to the highest level that can be consumed by humans. Lactatingmothers have a high risk of poisoning due to exposure to mercury from local food ingredients, while babies are exposed to mercury from their mothers during breastfeeding. Mercury in the blood of lactatingmothers will enter the breast blood circulation system and will accumulate in breast milk. Exposure to mercury in breast milk will accumulate in the baby's body and will have a health impact on the baby because the baby is very susceptible to the toxicity of heavy metals including mercury. This study aims to determine the effect of mercury exposure from food ingredients to the mercury content in the blood of lactatingmothers. Subjects were 35 breastfeedingmothers who lived in the gold mining area in Cineam, Tasikmalaya Regency. Exposure to mercury from food is obtained by the approach to the consumption of food collected by the semiquantitative food frequency method. The content of mercury in food ingredients and in the blood was analyzed with an Atomic Absorption Spectrophotometer. The results showed the average mercury content in eight types of food items ranged from 0,00063 - 0.73333 ppm, the average mercury exposure from food ingredients in the day between 0.0088 - 6.7955 ppm and the average mercury content in the blood of nursing mothers was 1 , 02880 ppm. The average mercury content in rice, pond fish, paddy fish, spinach, katuk leaves and banana are still below normal limits, while the mercury content in water spinach and genjer is above the established normal limit. The majority of lactatingmothers, 74.3%, had higher levels of mercury in their blood than normal limits. Statistical analysis with Spearman correlation showed that there was an influence of mercury exposure from food ingredients to the mercury content in the blood of lactatingmothers (p = 0.048; r = 0.286). Provision of information in the form of counseling and installation of posters around the gold mining site about efforts to prevent increased mercury accumulation in the body by avoiding the consumption of food derived from plants that live on the banks of the amalgamation river. Providing iron supplements to breastfeedingmothers to help prevent anemia caused by mercury exposure in the blood. Keywords: mercury exposure, mercury levelin the blood, lactatingmothers